PENGARUH GOOD GOVERNANCE, WHISTLEBLOWING SYSTEM, DAN PENGENDALIAN INTERNAL TERHADAP PENCEGAHAN FRAUD PADA PENGELOLAAN KEUANGAN DESA: STUDI KASUS KEUANGAN DANA DESA DI ARGOMULYO, KECAMATAN SEDAYU, KABUPATEN BANTUL - Clawdya Br Ginting, Chindy; As’ari, Hasim (Penerbit Lafadz Jaya, 2025)
This study aims to analyze the influence of Good Governance, the Whistleblowing System, and Internal Control on fraud prevention in village financial management. The research was conducted in Argomulyo Village, Sedayu District, Bantul Regency, using a quantitative approach. Data were collected through questionnaires distributed to 31 village officials directly involved in financial management. The data were analyzed using multiple linear regression with the assistance of SPSS. The results indicate that Good Governance, the Whistleblowing System, and Internal Control have a positive and significant effect on fraud prevention, both partially and simultaneously. These findings demonstrate that the implementation of sound governance practices, an effective reporting system, and strong internal controls can reduce the likelihood of fraudulent activities in village financial management. The application of transparency, accountability, and continuous supervision principles plays an essential role in strengthening integrity and public trust in village administration. Therefore, enhancing Good Governance practices, improving the effectiveness of the Whistleblowing System, and reinforcing Internal Control are strategic measures to prevent fraud and promote accountable and sustainable village financial governance.